Effect of Ginger (Zingiber officinale) on Performance and Blood Serum Parameters of Broiler - Mohamed , Arkan B.; Al-Rubaee, Mohammed A.M.; Jalil, Ali Q. (International Journal of Poultry Science, 2012)
This study was carried out at the Poultry of Animal Resource, College of Agriculture, Tikrit University. The present study was conducted to explore the usage of different levels of ginger at concentration of 0.1 and 0.2% respectively supplemented to diets on the Performance and blood serum traits of the Broiler Chickens. 180 (ROSS) 3 weeks old broiler chicks raised to 6 weeks of age. The birds were distributed into 3 treatment groups with three replicates per treatment (20 birds per replicate + 10 females). Ginger (Zingiber officinale) was supplemented at the rate 0.1 and 0.2% in the diets to treatments T2 and T3 respectively while treatment one served as control. The result of performance parameter showed significant difference between treatments. However body weight, weight gain, FCR and feed intake showed a significant differences (p<0.05) between T2 (0.1% ginger) and T3 (0.2% ginger) and control. The total protein didn’t differ significantly between the treatment groups. Serum cholesterol, triglyceride and glucose level was a significantly lower in the 0.1 and 0.2% of ginger (p<0.05) than control. Findings of the research study indicated that groups receiving ginger at the rate of 0.1 and 0.2% of the diets showed better performance and serum profiles in broiler.